The influence of video lectures on student engagement in the University of Cape Town's first Massive Open Online Course - Fife, Mary-Ann (School of Education, 2017)
This study set out to determine the role that video lectures played in engaging participants with different learning styles in UCT's first Massive Open Online Course (MOOC), Medicine and the Arts: Humanising Healthcare. A framework based on Grundewald's adaptation of Kolb's Learning Model was developed in order to segment students according to their learning styles and analyse the similarities and differences in their preferences for various video production styles (e.g. talking head, location-based videos, office based videos, visually illustrative videos etc.). Since prior research in this field has been largely quantitative to date and descriptive of behaviour but devoid of meaning, this study took a mixed methods, case study approach with the aim of studying the intent behind behaviours in MOOCs rather than the behaviour itself. Eight Skype interviews with students who participated in the course were conducted and analysed. These interviews were transcribed and analysed using thematic analysis. The analysis of this qualitative data was supported by survey data gathered at the beginning of the course (pre-course survey - 2 916 respondents), surveys conducted during each week of the course (411 responses over six weeks) as well as after the completion of the course (postcourse survey - 130 respondents). All surveys were administered via electronic survey collection tools (i.e. Google Forms and Survey Monkey) and included both closed and open-ended questions. The pre- and post-course surveys were administered by FutureLearn and the surveys sent during the course were administered by the researcher. The data from the survey was analysed using mainly simple descriptive and correlation techniques as well as a cluster analysis. One of the key findings was that MOOC participants relate to the presenters in MOOCs through the videos, and the presenter's style and approach had a strong influence on the students' engagement. In addition, while there was no definitive conclusion about the effect of learning styles on engagement, a preference for social engagement was found to be a major differentiator between the natural groupings identified by the cluster analysis conducted. Given that this was a case study, it is recommended that the findings are tested across platforms and types of courses in order to further refine the results of this research and reduce bias.